New Antarctic findings of Upper Cretaceous and lower Eocene loons (Aves: Gaviiformes) - Acosta Hospitaleche, Carolina Ileana Alicia; Gelfo, Javier Nicolás (Annales de Paléontologie)
The new remains of Gaviiformes collected from the Maastrichtian Sandwich Bluff Member (López de Bertodano Formation in Vega Island), the Maastrichtian Klb 9 (López de Bertodano Formation in Seymour Island), the Maastrichtian Snow Hill Formation (Vega Island), and the Ypresian Submeseta Formation (Seymour Island), Antarctica, are described. A specialized foot-propelled diving morphology is already present in the Antarctic Polarornis gregorii, the Chilean Neogaeornis wetzelli and the new specimens here reported, suggesting that such diving skills were developed at least since the Upper Cretaceous. The occurrence of Gaviiformes in the Southern Hemisphere during the Upper Cretaceous-lower Eocene times is consistent with recent phylogenetic proposals relating this group to Sphenisciformes and Procellariiformes, birds already recorded in Antarctica. The fossil record also supports the idea that the hemisphere displacement observed in Gaviiformes could be a response to increasing competition for resources with Sphenisciformes. The phylogenetic proximity of penguins and loons plus their similar trophic behavior, suggest that competitive exclusion could have triggered the gaviiform migration to the Northern Hemisphere and explain their extinction from Southern continents. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Gelfo, Javier Nicolás. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina